2017
DOI: 10.1007/s00417-017-3584-2
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma drainage device surgery in children and adults: a comparative study of outcomes and complications

Abstract: PurposeTo compare the postoperative outcomes and complications of glaucoma drainage device (GDD) surgery in pediatric (<18 years old) and adult patients.MethodsRetrospective, comparative study including all patients who underwent Baervedlt or Molteno device surgery by the same surgeon. Success criteria included postoperative intraocular pressure (IOP) between 6 and 21 mmHg and a 20% reduction from baseline.ResultsFifty-two children (69 eyes) and 130 adults (145 eyes) were included. Mean IOP and number of medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 20 publications
1
31
1
1
Order By: Relevance
“…However, non-valved shunts have a greater 5-year risk of hypotony and its related complications when compared to valved shunts [5,6]. Although early hypotony following non-valved GDDs has been reported to occur in as much as 39% of eyes [3,7], the incidence of persistent hypotony is far less common, with reports in the literature ranging from 0% to 13%, which is in keeping with our rate of 4.4% [6,[8][9][10]. The variation is likely to be due to a difference in case-mix between studies, with those studies having higher proportions of complex eyes (chronic uveitis, trauma, prior cyclo-destructive procedures or neovascular glaucoma) being more likely to have greater rates of persistent hypotony.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, non-valved shunts have a greater 5-year risk of hypotony and its related complications when compared to valved shunts [5,6]. Although early hypotony following non-valved GDDs has been reported to occur in as much as 39% of eyes [3,7], the incidence of persistent hypotony is far less common, with reports in the literature ranging from 0% to 13%, which is in keeping with our rate of 4.4% [6,[8][9][10]. The variation is likely to be due to a difference in case-mix between studies, with those studies having higher proportions of complex eyes (chronic uveitis, trauma, prior cyclo-destructive procedures or neovascular glaucoma) being more likely to have greater rates of persistent hypotony.…”
Section: Discussionmentioning
confidence: 99%
“…We used Mitomycin C (MMC) during GDD implantation in 83% of eyes in this series, based on a previous study that demonstrated that intraoperative use of MMC was not significantly associated with hypotony or low IOP at 3 and 5 years [3]. Our experience is that early hypotony within the first 3 months is due to over-drainage rather than MMC use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Es ist denkbar, dass dies die postoperative Fibrosierung der Tenonkapsel beeinflusst. Die Langzeitergebnisse der AVB-und ABC-Studie bei Erwachsenen zeigen zumindest eine bessere Drucksenkung mit dem Baerveldt-Implantat [31,32] [34,35,37,40]. Bei jugendlichen oder erwachsenen Patienten kann, je nach Voroperationen (Aphakie, Z. n. Vitrektomie), eine alternative Schlaucheinlage, z.…”
Section: Drainageimplantateunclassified
“…Known complications of GDD surgery include intraocular bleeding, choroidal detachment, erosion of the conjunctiva, hypotony, corneal decompensation, strabismus, tube obstruction, tube exposure, and infection [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%